Language, Identity and the Dynamics of Language Shift in Mallorca - Guasp, Felipe Pieras (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 2000)
This paper questions the premise that social identity and ethnicity are established mainly through language and argues for a subjective approach to determine individual self-ascription. Data from two investigations carried out in 1997 and 1998 in Palma, Spain, show that a) interaction between Catalan speakers and Spanish speakers generally takes place in Spanish; b) Catalan is mainly used as a symbol of identity rather than as a neutral code for communication; and c) Spanish speakers can and do use criteria other than language to identify their local social ascription. These factors prevent Catalan from becoming an ethnically unmarked and fully normalised language. A change in linguistic norms appears as an appropriate method of weakening the link between Catalan and a local identity.